Carvings on the parapet wall - sequences from Mahabharata - Khandava forest burning - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] If you observe the relief, you can see the arrows on top. Arjuna in order to help Agni, the God of fire, creates an umbrella of arrows to prevent Indra, the God of thunderstorm, from dousing the fire.